2018
DOI: 10.1016/j.nmd.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional analysis of clinical evaluation in 35 individuals with mutations of the valosin-containing protein gene

Abstract: Inclusion body myopathy (IBM) associated with Paget disease of the bone and frontotemporal dementia or IBMPFD is an autosomal dominant degenerative disorder caused by mutations in the valosin-containing protein (VCP) gene. We aim to establish a detailed clinical phenotype of VCP disease amongst 35 (28 affected individuals, 7 presymptomatic gene carriers) individuals versus 14 unaffected first-degree relatives in 14 families to establish useful biomarkers for IBMPFD and identify the most meaningful tests for mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 62 publications
3
18
0
Order By: Relevance
“…Both questionnaire and examination including IBMFRS/MRC scale suggested involvement of both proximal/distal muscle weakness and predominance of the lower extremity weakness without any muscle sparing. In a previous study, correlation between IBMFRS and MRC scale/fatigue scale/6-min walk test in patients with mutations of the VCP gene was detected [27]. The results in this study also support the idea that IBMFRS may correlate with MRC scale in that both suggested the predominance of the lower extremity weakness and that the IBMFRS could be useful for assessing the muscle weakness in the patients with VCP gene mutations.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Both questionnaire and examination including IBMFRS/MRC scale suggested involvement of both proximal/distal muscle weakness and predominance of the lower extremity weakness without any muscle sparing. In a previous study, correlation between IBMFRS and MRC scale/fatigue scale/6-min walk test in patients with mutations of the VCP gene was detected [27]. The results in this study also support the idea that IBMFRS may correlate with MRC scale in that both suggested the predominance of the lower extremity weakness and that the IBMFRS could be useful for assessing the muscle weakness in the patients with VCP gene mutations.…”
Section: Discussionsupporting
confidence: 85%
“…In French and Spanish cohort, 29% of the patients showed a forced vital capacity under 70% of the predicted value [2]. In a second study, the forced vital capacity as a percentage of the individual's reference value, was 84.44 ± 29.53 (mean ± SD, %) [27]. The results in this study also suggest the effect on inspiratory muscles and respiratory function should be monitored regularly.…”
Section: Discussionsupporting
confidence: 48%
“…A recent study by Al-Obeidi et al (2018) showed that VCP mutations are present in ∼9% of ALS, 4% of Parkinson's disease, and 2% of Alzheimer's disease patients. As of today, no definite correlation between the mutation type and the incidence of clinical features associated with VCP has been established (Al-Obeidi et al, 2018;Plewa et al, 2018).…”
Section: Valosin Containing Protein (Vcp)mentioning
confidence: 99%
“…Grip strength measurements using the Jamar handheld dynamometer (Patterson Medical) was obtained at five time points at UC Irvine Institute of Clinical Translational Science (ICTS), and at weekly intervals by the patient using a Camry® EH101 electronic hand dynamometer. Dynamometry is an effective for assessing isometric limb strength and is correlated with the IBMFRS scale [4,7].…”
Section: Grip Strength Dynamometrymentioning
confidence: 99%
“…Frontotemporal dementia which occurs at a mean age of 55 years in 30% of IBMPFD patients often results in early death; however, those with myopathy may have several decades of increasing weakness and loss of mobility. IBMPFD is highly penetrant and is typically considered if two or more of the typical features or suggestive family history is present [4]. There is currently a lack of information on the long-term progression of this disease.…”
Section: Introductionmentioning
confidence: 99%